CTNNB1 45F mutation is a molecular prognosticator of increased postoperative primary desmoid tumor recurrence: An independent, multicenter validation study. Issue 20 (31st July 2013) - Colombo, Chiara; Miceli, Rosalba; Lazar, Alexander J.; Perrone, Federica; Pollock, Raphael E.; Le Cesne, Axel; Hartgrink, Henk H.; Cleton‐Jansen, Anne‐Marie; Domont, Julien; Bovée, Judith V. M. G.; Bonvalot, Sylvie; Lev, Dina; et al.
Abstract : BACKGROUND: A role for the serine to phenylalanine substitution at codon 45 (the S45F mutation) in the catenin (cadherin‐associated protein) β‐1 ( CTNNB1 ) gene as a molecular predictor of local recurrence in patients with primary, sporadic desmoid tumor (DT) has been reported. To confirm the previous data, the authors evaluated the correlation between CTNNB1 mutation type and local recurrence in this multi‐institutional, retrospective study. METHODS: Patients with primary, sporadic DT who underwent macroscopic complete surgical resection were included. Recurrence‐free survival (RFS) analyses were conducted using the Kaplan‐Meier method and log‐rank tests to compare strata. RESULTS: In total, 179 patients were identified, including 65% females and 35% males (median age, 39 years; median tumor size, 7 cm). Most DTs were located in the abdominal/chest wall (42%) followed by extra‐abdominal sites (40%) and intra‐abdominal sites (18%). All patients underwent either R0 resection (62%) or R1 resection (38%), and most underwent surgery alone (80%). The tyrosine to alanine substitution at codon 41 (T41A) was the most frequent mutation (45%), but the S45F mutation was more prevalent in extra‐abdominal DTs compared with other sites ( P  < .001). At a median follow‐up of 50 months, 86% of patients remained alive without disease. The estimated 3‐year and 5‐year RFS rates were 0.49 and 0.45, respectively, for patients who had tumors with the S45F mutation; 0.91 and 0.91, respectively, for patients who had wild‐type tumors; and 0.70 and 0.66, respectively, for all others ( P  < .001). A similar trend was observed for patients who underwent surgery alone ( P  < .001). On multivariable analysis, mutation remained the only factor that was prognostic for local recurrence. CONCLUSIONS: This series confirmed that primary, completely resected, sporadic DTs with the S45F mutation have a greater tendency for local recurrence. With increasing implementation of "watchful‐waiting" for DT management, it will be important to determine whether mutation type predicts outcome for these patients. Cancer 2013;119:3692–3702 . © 2013 American Cancer Society . Abstract : Primary and completely resected desmoid tumors with the CTNNB1 S45F mutation exhibit a greater tendency for local recurrence. With the increasing implementation of a "watchful‐waiting" policy as part of desmoid tumor management, it will be important to determine whether mutation type predicts the course of such untreated patients to potentially tailor their treatment.